"It's not a calculator thingy because a calculator can't answer the question": multilingual children's mathematical reasoning. Issue 2 (4th May 2019) - Assaf, Fatima; Graves, Barbara
ABSTRACT: Drawing on sociocultural theories, this study considers the multiple resources multilingual children use to communicate mathematically. We engaged with three children and a parent, in order to understand how multilingual children express their mathematical reasoning. The family was given a mathematical problem solving activity designed to encourage discussion so that we would have access to the children's reasoning. To analyse their reasoning, we drew on established informal reasoning categories. In our analysis, we found that the number of claims far outweighed the other reasoning categories. These claims were linked by conditional relations, which suggests that the children were developing a form of argument supported by evidence. The source of evidence came primarily from the problem instructions, and the children's mathematical and world knowledge.